(untitled) (Experimental biology, 2017)
It was study the common lipid content in mono- and mixed culture of green algae. Three monoculture which the lipids is maximum: Nautococcopsis constricta, Selenastrum gracilis, Dictyochlorella globosa. Mixed cultivation Nautococcopsis constricta and Dictyochlorella globosa, and Nautococcopsis constricta and Selenastrum gracilis increased lipid mass nearly 1.4 times after 7 days of cultivation.